Plan de marketing para la embotelladora y distribuidora “Liqui Agua” del cantón El Empalme - Huilcapi Pazmiño, Luis Alberto (2013)
Currently increasing local competitors that offer bottled water quality at popular price low and the presence of powerful brands that have a high prestige that invest a large budget for promotion and advertising their products originate decrease in profit margin in the past months in the Distribution and Bottling LIQUI WATER. First we conducted a market survey to determine the behavior of our target audience, which are the company's customers and end users. We applied a sample of 345 and 100 surveys were distributed to the company's customers and 245encuestas for consumers and their choice was randomly distributed it using purposive sampling technique for the experience of the researcher. Currently the company competes with other products also offer the same features and high economic power, 76% of customers if they have offers from other companies while 24% said they received no other offers. This shows how fragile the portfolio of customers that the company has LIQUI WATER. When we investigate the importance of product quality as bottled water corresponds to the highest percentage was considered very important with 58% followed closely the remaining 42% with the major alternative. This result shows the importance to product quality and the need to strengthen the brand. It was recommended to improve the presentation of the brand with images and colors to overcome creative presentations of other brands Benchmarkingy applying a strategy to change the image of the brand LIQUI WATER based on a new concept of product quality with new added values that attract most demanding customers.